Aquaporin Water Channels and Hydrocephalus - Verkman, Alan S. (Pediatr Neurosurg, 2017)
The aquaporins (AQPs) are a family of water-transporting proteins that are broadly expressed in mammalian cells. Two AQPs in the central nervous system, AQP1 and AQP4, might play a role in hydrocephalus and are thus potential drug targets. AQP1 is expressed in the ventricular-facing membrane of choroid plexus epithelial cells, where it facilitates the secretion of cerebrospinal fluid (CSF). AQP4 is expressed in astrocyte foot processes and ependymal cells lining ventricles, where it appears to facilitate the transport of excess water out of the brain. Altered expression of these AQPs in experimental animal models of hydrocephalus and limited human specimens suggests their involvement in the pathophysiology of hydrocephalus, as do data in knockout mice demonstrating a protective effect of AQP1 deletion and a deleterious effect of AQP4 deletion in hydrocephalus. Though significant questions remain, including the precise contribution of AQP1 to CSF secretion in humans and the mechanisms by which AQP4 facilitates clearance of excess brain water, AQP1 and AQP4 have been proposed as potential drug targets to reduce ventricular enlargement in hydrocephalus.